2019
DOI: 10.1103/physrevmaterials.3.054405
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of polar displacements and conduction in doped ferroelectrics: An ab initio comparative study

Abstract: Polar metals are rare because free carriers in metals screen electrostatic potential and eliminate internal dipoles. Degenerate doped ferroelectrics may create an approximate polar metallic phase.We use first-principles calculations to investigate n-doped LiNbO 3 -type oxides (LiNbO 3 as the prototype) and compare to widely studied perovskite oxides (BaTiO 3 as the prototype). In the rigid-band approximation, substantial polar displacements in n-doped LiNbO 3 persist even at 0.3 e/f.u. ( 10 21 cm −3 ), while p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
2
15
0
1
Order By: Relevance
“…(about 1.6 × 10 21 cm −3 ), at which the polar displacement δ is just completely suppressed and the c / a ratio is reduced to unity. This result is consistent with the previous theoretical studies 36 , 37 . Experimentally, in metallic oxygen-deficient BaTiO 3− δ , the low-symmetry polar structure can be retained up to an electron concentration of 1.9 × 10 21 cm −3 (close to the theoretical result) 44 , 45 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…(about 1.6 × 10 21 cm −3 ), at which the polar displacement δ is just completely suppressed and the c / a ratio is reduced to unity. This result is consistent with the previous theoretical studies 36 , 37 . Experimentally, in metallic oxygen-deficient BaTiO 3− δ , the low-symmetry polar structure can be retained up to an electron concentration of 1.9 × 10 21 cm −3 (close to the theoretical result) 44 , 45 .…”
Section: Resultssupporting
confidence: 94%
“…Motivated by the above experiments and theories, we use first-principle methods with no adjustable parameters to demonstrate a large modulation of electron-phonon coupling in doped strong ferroelectrics by utilizing soft polar phonons. We study BaTiO 3 as a prototype, because (1) previous studies found that in n -doped BaTiO 3 , increasing the carrier density gradually reduces its polar distortions and induces a continuous polar-to-centrosymmetric phase transition 36 , 37 ; and (2) the critical concentration for the phase transition is about 10 21 /cm 3 , which is high enough so that the electron-phonon coupling can be directly calculated within the Migdal’s approximation (in contrast, in doped SrTiO 3 , superconductivity emerges at a much lower carrier concentration 10 17 –10 20 /cm 3 so that its Debye frequency is comparable to or even higher than the Fermi energy ℏ ω D / ϵ F ~ 1 − 10 2 38 , which invalidates the Migdal’s approximation and Eliashberg equation) 29 . The key result from our calculation is that, contrary to Anderson/Blount’s argument for "ferroelectric-like metals” 32 34 , we find that the phonon bands associated with the soft polar optical phonons are strongly coupled to itinerant electrons across the polar-to-centrosymmetric phase transition in doped BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…3e and f show the electronic band structures of conducting and insulating oxygen-deficient LiNbO 3−δ , respectively. In conducting LiNbO 3−δ , the band width of the defect state is reduced by hydrostatic pressure, which is in contrast to pristine LiNbO of doped electrons is highly inhomogeneous [26]. As we showed previously in Fig.…”
Section: B Pressure Effects On Oxygen-deficient Batio 3−δ and Linbo 3−δmentioning
confidence: 54%
“…However, different from pristine LiNbO 3 , there is a sudden "jump" in the polar displacements between 7 and 8 GPa, which is evident in the inset of panel d. For a given hydrostatic pressure, the average polar displacements of conducting oxygendeficient LiNbO 3−δ are slightly smaller than those of pristine LiNbO 3 . This is because mobile electrons in conducting LiNbO 3−δ can screen internal electric fields and suppress the polar displacements [26]. However, in insulating LiNbO 3−δ , the average polar displacements are almost the same as those of pristine LiNbO 3 because screening from mobile electrons is absent.…”
Section: B Pressure Effects On Oxygen-deficient Batio 3−δ and Linbo 3−δmentioning
confidence: 98%
“…À1 ), implying that the structural transition temperature of BPTO is higher than that of LiOsO 3 40 . We note that the above second-order structural phase transition is a key property to distinguish instrinsic polar metals from degenerately doped ferroelectrics [32][33][34][35]41,42 , because realistic dopants (cation substitution or oxygen vacancies) make the crystal symmetry of doped ferroelectrics ill-defined and correspondingly there is no well-defined continuous structural phase transition at finite temperatures.…”
Section: Resultsmentioning
confidence: 99%